2016
DOI: 10.1080/09168451.2015.1062715
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in studies on the health benefits of pyrroloquinoline quinone

Abstract: Pyrroloquinoline quinone (PQQ), an aromatic tricyclic o-quinone, was identified initially as a redox cofactor for bacterial dehydrogenases. Although PQQ is not biosynthesized in mammals, trace amounts of PQQ have been found in human and rat tissues because of its wide distribution in dietary sources. Importantly, nutritional studies in rodents have revealed that PQQ deficiency exhibits diverse systemic responses, including growth impairment, immune dysfunction, and abnormal reproductive performance. Although P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 97 publications
(124 reference statements)
1
86
0
Order By: Relevance
“…cardio-protection (Akagawa et al, 2015;Rucker et al, 2009). We showed here the unexpected efficacy of PQQ, in which lifespan can be extended by generating ROS at the plasma membrane.…”
Section: Pqq Is a Lifespan Extension Chemical With A Novel Action Mecmentioning
confidence: 74%
See 2 more Smart Citations
“…cardio-protection (Akagawa et al, 2015;Rucker et al, 2009). We showed here the unexpected efficacy of PQQ, in which lifespan can be extended by generating ROS at the plasma membrane.…”
Section: Pqq Is a Lifespan Extension Chemical With A Novel Action Mecmentioning
confidence: 74%
“…Because PQQ regulates the activity of redox enzymes (Akagawa et al, 2015;Anthony and Zatman, 1967;Hauge, 1964;Rucker et al, 2009;Salisbury et al, 1979), we focused on BLI-3, a C. elegans ortholog of the mammalian dual oxidases, DUOX1 and DUOX2 (Brenner, 1974;Edens et al, 2001). PQQ did not extend the lifespans of three reduction-of-function bli-3 mutants, bli-3(im10), bli-3(e767) and bli-3(n529) ( Fig.…”
Section: Pqq Administration To Adult C Elegans Extends Lifespanmentioning
confidence: 99%
See 1 more Smart Citation
“…For example: it has been reported that PQQ functions as a potent cofactor in certain bacterial dehydrogenases (Flores-Encarnación et al, 2004). In animal cells, PQQ is involved in different signal transduction processes during cell growth, development, differentiation and cellular survival (Akagawa et al, 2016;Feng et al, 2014;Kimura et al, 2012). It has been reported that PQQ is a potent antioxidant (50-100 times more effective than ascorbic acid) (Rucker et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PQQ is a potent antioxidant (50-100 times more effective than ascorbic acid) (Rucker et al, 2009). It has been also reported that PQQ can function as a protector in cardiac lesions, prevents liver injury by eliminating free radicals, stimulates astrocytes and inhibits the generation of melanocytes in melanoma (Akagawa et al, 2016;Feng et al, 2014;Jia et al, 2015;Murase et al, 1993;Sato and Toriyama, 2009;Tao et al, 2007). In animal models, it has been shown that when PQQ is added to the diet (300 μg/kg body weight), reproduction and neonatal rates in rats and mice were increased (Harris et al, 2013).…”
Section: Introductionmentioning
confidence: 99%